ANALISIS TIPOLOGI DAN HUBUNGAN ANTARA INDEKS PEMBANGUNAN MANUSIA DAN PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA SELATAN - Bambang Bemby Soebyakto; Abdul Bashir (Jurnal Ekonomi Pembangunan, 2015)
The aim of this research is to seen the dynamic of economic growth within two types of typology year of 2007-2012, and the connection patter of economic growth and Human Development Index in Province of South Sumatera. Analyzing methods which used in this research are qualitative and quantitative descriptive analysis, research by Klassen typology analysis technique, and Rank Spearman Correlation. The result can be concluded if economic growth typology and HDI showed that (1) region which include in high level economic growth and HDI classification is Palembang. This also strengthen Palembang top position in region competing level; (2) regions which in the second quadrant with low level economic growth and HDI classification are District of Lahat, Ogan Komering Ilir, Banyuasin, East OKU, and also the city of Lubuk Linggau; (3) regions which in high level of HDI classification, but low level in economic growth are District of South OKU, Ogan Komering Ulu, the city of Pagar Alam, and also Prabumulih; (4) on the other hand District of Musi Banyuasin, Muara Enim, Ogan Ilir, and Musi Rawas included as low level of economic growth and HDI. The mathematical result showed that the role of district or city economic growth is not supported to push up the level of economic growth. It showed from the value of r = 0.600 or equal to 60 percent. The low role of human resource to economic growth indicated the low intention from the government to the human resource development. Keywords: Human Development Index, Economic Growth, Typology, Spearman Correlation.